Nurse Perception in Metabolic Syndrome - Fatimah Abdullah Al Bin Diraa; Zainab Abdulwhab Alrashed; Habib Hussien Al Musharaf; Fatimah Saleh Alghanem; Rajaa Mohammed Al Saleh; Wadeah Ibrahim Al Abdullatif; Ahmed Taher Albinmaan; Ismail Ibrahim Alhmud; Abdullah Hashim Alsuwayj; Hani Ali Alsalem; Abdullah Salah Almthin; Hydr Abdullah Alsalman; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Metabolic syndrome is a cluster of metabolic abnormalities associated with an increased risk of cardiovascular disease and type 2 diabetes. Nurses play a crucial role in the prevention, management, and education of patients with metabolic syndrome. This review explores nurses' perceptions of metabolic syndrome, including their understanding of its etiology, risk factors, clinical manifestations, and nursing interventions. The challenges faced by nurses in caring for patients with metabolic syndrome are discussed, along with strategies to improve patient outcomes and reduce the burden of metabolic syndrome on healthcare systems. Key words: Metabolic syndrome, T2DM, obesity.